Elucidating the Clusia criuva species 'complex': cryptic taxa can exhibit great genetic and geographical variation - Cortez, Maria Beatriz De S.; Sforca, Danilo A.; Alves, Fabio De M.; Vidal, Joao De D. [UNESP]; Alves-Pereira, Alessandro; Mori, Gustavo M. [UNESP]; Andreotti, Isabela A.; Do Nascimento, Jose E.; Bittrich, Volker; Zucchi, Maria I.; Amaral, Maria Do Carmo E.; De Souza, Anete P. (Oxford Univ Press, 2019)
In the Clusia criuva Cambess. species complex, the two subspecies C. criuva subsp. parviflora Vesque and C. criuva subsp. criuva can only be distinguished on the basis of stamen/staminode morphology and geographical occurrence. Despite being recently restructured, taxonomic relationships in this complex remain unclear. Therefore, to illuminate the evolutionary mechanisms involved in the diversification of these two lineages we investigated their population structure, phylogeographical and niche distribution patterns using plastid and nuclear microsatellites (plastid SSRs and nuSSRs, respectively). We obtained ten polymorphic nuSSRs from a microsatellite-enriched library and used six previously described plastid SSRs to genotype c. 300 samples. We conducted F-statistics, genetic distance and population structure analyses to test whether the subspecies presented distinct genotypic clusters. Putative phylogeographic breaks were also identified and tested. Finally, we developed distribution models to contrast genetic and environmental information. We found extensive genetic differentiation between the subspecies. Three significant breaks were identified, two of which coincide with geographical barriers. Niche modelling predictions indicated that C. criuva subsp. criuva potentially occupied a much wider area during the Last Glacial Maximum than it does today. These results indicate that both lineages are evolving independently because of limited gene flow and restriction to different environments, suggesting that they should again be elevated to species status. To clarify this issue, we recommend further phylogenetic and morphological studies.
Keywords: microsatellite markers; niche modelling; phylogeography; population genetics; speciation